A procurement model for electronic markets. (14th November 2006) - Hazra, Jishnu; Mahadevan, B.
Electronic markets provide an alternative channel for industrial procurement. However, there are alternative viewpoints on the impact of electronic market on the procurement practice of firms. While some argue that the number of suppliers selected for award of contract could increase, several others predict that the number of suppliers will decrease. We investigate this issue by modelling the procurement process in an electronic market. We explicitly model the coordination costs of dealing with selected suppliers in an electronic market. We analyse alternative coordination cost functions and develop solutions for the procurement policy that managers should adopt. Our results show that inclusion of coordination costs in the analysis is significant in the decision-making framework. We further show that managers do not gain much by prequalifying a large pool of suppliers to participate in the procurement process. Furthermore, we also found that variations in supplier capacities do not significantly affect the optimum number of suppliers when there are costs of coordination.